1987
DOI: 10.1016/0035-9203(87)90240-9
|View full text |Cite
|
Sign up to set email alerts
|

Pyrimethamine-sulfadoxine still effective against Plasmodium falciparum in Jayapura, Irian Jaya: RI-type resistance in 2 of 18 patients

Abstract: The sensitivity of Plasmodium falciparum infections to pyrimethamine-sulfadoxine was studied in 18 Indonesian patients in Jayapura, Irian Jaya. In 16 of the 18 patients parasitaemia was cleared by day 6 and the patients remained without parasitaemia through day 28. Two of the 18 patients had late recrudescences consistent with RI-type resistance; one each on days 14 and 21. Pyrimethamine-sulfadoxine is still an effective antimalarial for most patients with falciparum malaria in Jayapura.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 5 publications
0
8
0
Order By: Relevance
“…All 50 chloroquine-resistant samples carried the mutant pfcrt 76T allele. No mutation was detected at codon 73, but variations were found at codons 72, 74, and 75 in 50 samples: SVMNT (24), CVIET (11), CVMNT (9), and SVIET (6). Statistical analysis (chi-square test with Yates' correction) showed that the pfcrt mutation at codon 76 was strongly associated with chloroquine resistance (P < 0.0001).…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…All 50 chloroquine-resistant samples carried the mutant pfcrt 76T allele. No mutation was detected at codon 73, but variations were found at codons 72, 74, and 75 in 50 samples: SVMNT (24), CVIET (11), CVMNT (9), and SVIET (6). Statistical analysis (chi-square test with Yates' correction) showed that the pfcrt mutation at codon 76 was strongly associated with chloroquine resistance (P < 0.0001).…”
Section: Resultsmentioning
confidence: 96%
“…4,5 An increased risk of chloroquine resistance was reported from the Jayapura region of Papua, Indonesia in the1980s. 6,7 Surveys conducted during the 1990s showed high malaria prevalence rates (60−92%) and levels of chloroquine treatment failure of up to 80% among indigenous and immigrant communities of northern and central Papuan Indonesia. 8−12 However, due to its safety profile, low cost, and relative success in treating mildly symptomatic malaria infections among immune and semi-immune patients, chloroquine remains the treatment of choice for malaria, and no effective alternative strategy has been developed.…”
Section: Introductionmentioning
confidence: 99%
“…29,30 With the exception of one study conducted in Papua (formerly Irian Jaya), where SP treatment failure rates were greater than 50%, 31 the SP treatment success rate observed in this trial is similar to that observed in other SP treatment trials conducted in eastern Indonesia. [32][33][34] In western Indonesia, rea-sonably good efficacy is reported for SP in central Java (78% treatment success at day 28) 35 which contrasted dramatically with a 83% failure rate observed for SP treatment of uncomplicated P. falciparum malaria in Nias Island in northern Sumatra. 36 The success of antimalarial treatment is influenced by many factors.…”
Section: Discussionmentioning
confidence: 98%
“…Rumans et al first reported P. falciparum resistance to SP in 1979 in Jayapura (Papua; Rumans et al, 1979). Since then, Hoffman et al have conducted tests in Jayapura (Papua), revealing resistance in 5% (2/41) and 11% (2/18) of cases, in 1983 and 1984, respectively (Hoffman et al, 1985, 1987).…”
Section: 2 Epidemiology Of Malariamentioning
confidence: 99%